2012
DOI: 10.1186/1475-9276-11-48
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in health care utilisation in Norway: the population-based HUNT3 survey

Abstract: BackgroundIn this study we investigated the distribution of self-reported health care utilisation by education and household income in a county population in Norway, in a universal public health care system based on ideals of equal access for all according to need, and not according to wealth.MethodsThe study included 24,147 women and 20,608 men aged 20 years and above in the third Nord-Trøndelag Health Survey (HUNT 3) of 2006–2008. Income-related horizontal inequity was estimated through concentration indexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 18 publications
9
67
2
Order By: Relevance
“…In general, the Norwegian universal public health care system is based on a principle of equal access for all citizens according to needs, and not according to wealth. However, a recently published Norwegian study on self-reported health care utilization in the general population found social inequalities in utilization of specialized health care services [32]. …”
Section: Discussionmentioning
confidence: 99%
“…In general, the Norwegian universal public health care system is based on a principle of equal access for all citizens according to needs, and not according to wealth. However, a recently published Norwegian study on self-reported health care utilization in the general population found social inequalities in utilization of specialized health care services [32]. …”
Section: Discussionmentioning
confidence: 99%
“…However, studies also indicate that this high utilization is mainly explained by the greater health care needs among the poor, and when such differential needs are taken into account, utilization instead favors the well-off [15, 16]. This pattern of overutilization of outpatient care among the rich relative to the poor differs from findings in other Scandinavian countries [17, 18] and most OECD countries [16, 19], where no horizontal inequities have been found after taking health care needs into account. Nevertheless, Swedish and international research has focused on adults [14, 15] or elderly [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the volume of articles differed between chronic diseases: 59 articles (79.7 %) included oncology samples [19, 3240, 4247, 5055, 5763, 6572, 74, 7696]; 12 articles (16.2 %) included depression [32, 33, 41, 62, 64, 75, 83, 93, 97100]; 10 articles (13.5 %) included diabetes [18, 32, 33, 64, 74, 75, 83, 101–103]; 10 articles (13.5 %) included ischaemic heart disease [18, 32, 33, 48, 56, 64, 74, 75, 83, 102]; 7 articles (9.5 %) included COPD [32, 33, 49, 56, 74, 75, 102]; 7 articles (9.5 %) included asthma [18, 32, 33, 64, 74, 75, 83]; 6 articles (8.1 %) included arthritis [32, 33, 7375, 83]; and 3 articles (4.1 %) included osteoporosis [7375]. A total of 12 studies (16.2 %) included more than one disease of interest [18, 32, 33, 56, 62, 64, 7375, 83, 93, 102].…”
Section: Resultsmentioning
confidence: 99%